A Critical Analysis Of Dai Ethnic Characteristics In Five Movement Piano Suite In Scenes From Xishuangbanna By Xia Liang - Liang, Yikeng (2025)
This study explores the integration of dai ethnic music characteristics in xia liang’s composition, scenes from xishuangbanna, within the context of yunnan piano music. The aim of this research is to provide a detailed analysis of how traditional dai musical elements are incorporated into contemporary chinese piano compositions. The study employs both western and eastern music analysis methods. Western music analysis, guided by persichetti (1961) and kostka & santa (2018), examines the use of quartal and quintal harmonies, the lydian mode, chromaticism, and rhythmic and melodic structure. For the eastern music analysis, the works of zhang (2006) and xie & xie (2012), presented a fitting framework to analyse the application of dai music characteristics, such as san ban (free tempo) rhythms, san du (third interval/3rd), and mixed meters. These combined methods facilitated a comprehensive examination of the musical structure, harmonic language, rhythmic patterns, and melodic features in scenes from xishuangbanna.